A double-blind, placebo-controlled trial of the efficacy and safety of two doses of azelastine hydrochloride in perennial allergic rhinitis - Bousquet, Jean; Klimek, Ludger; Kuhl, Hans-Christian; Nguyen, Duc Tung; Ramalingam, Rajesh Kumar; Canonica, G. W.; Berger, William E. (Frontiers in Allergy, 2023)
Background Azelastine hydrochloride (AZE) is a selective, non-sedating H1 antagonist with anti-inflammatory and mast cell stabilizing properties, which can be used as an alternative to intranasal corticosteroids. The objective of this study was to evaluate the efficacy of the new formulation of 0.15% AZE compared to that of the placebo at a dosage of two sprays per nostril twice daily for 4 weeks in patients with perennial allergic rhinitis (PAR). Materials and methods A total of 581 subjects were randomized in this double-blind (DB) placebo-controlled trial (NCT00712920) that compared 0.10% (1,096 μg daily) and 0.15% AZE (1,644 μg daily) to the placebo in PAR patients. The study consisted of a 7-day single-blind placebo lead-in period and a 28-day DB treatment period. The primary endpoint was the change from baseline in the 12-h reflective total nasal symptom score (rTNSS) for the entire 28-day study period of 0.15% AZE, two sprays per nostril BID compared to the placebo. The efficacy and safety of 0.15% AZE were compared to the placebo. Results Least square (LS) mean improvement from baseline in the morning (AM) and evening (PM) combined rTNSS was statistically significant for the 0.15% AZE group (p = 0.04) compared to the placebo group. LS mean improvement from baseline in the AM and PM combined rTNSS was 4.10 (4.26) units for 0.15% AZE and 3.81 (3.99) for 0.10% AZE. For individual symptoms, there was a statistically significant change in the LS mean (p = 0.04) improvement from baseline on the 12-h reflective assessment for the 0.15% AZE group for runny nose. Further numerical improvements were shown for itchy nose, nasal congestion, runny nose, and sneezing compared to the placebo. No deaths or serious adverse events related to the study medication were reported. Conclusion The present formulation of 0.15% AZE is safe and effective in relieving PAR symptoms. It effectively relieves nasal and non-nasal symptoms. Clinical Trial Registration ClinicalTrials.gov, identifier: NCT00712920.